SURVEY PENYAMPAIAN MATERI PENDIDIKAN KESEHATAN SEMESTER GENAP 2012/2013 PADA MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SEKOLAH (STUDI PADA KELAS VIII DI SMP/MTS SE-KECAMATAN KENCONG-JEMBER) - NIZAR ALI, GHULAM (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical and sport education is one of the subjects given in school from the basic level in elementary school until high school, even in college. Physical and sport education in school puts the priority on the students activation in the movement aspect, howefer it does not mean that the other aspect is ignore. In the National Education System No. 19 Year 2005 is mentioned that the aims of the of sportmanship quality and awarenes of healthy life. In the National Education System No. 19 Year 2005 above, has been explained that physical and sport education subject does not only contain physical activity, but also healthy aspect which have to be conveyed to the students in order to reach the main purpose of the National Education. The purpose of this research are to know : 1) has the physical and sport education teacher given the healthy education materials in SMP in Kencong-Jember which is approriate with UU RI No. 19 Th. 2005 about National Education Standard; 2) the process of the providing health education material related to the method which is used in physical and sport education subject in SMP in Kencong-Jember; 3) the process of the providing health education subject in SMP in Kencong-Jember; 4) the process of the providing health education materia related to the evaluation system which is used in physical and sport education subject in SMP in Kencong-Jember; 5) the process of providing health education material related to the handbook which is used in physical and sport education subject in SMP in Kencong-Jember. Method which is used in this research is Descriptive Qualitative. While, the population in this research is the penjasorkes teacher and students which study in Junior School in Kencong-Jember. The result of this research is the conveying of materials of health education in Penjasorkes subject which has not worked has not worked maximally yet. It is because the Penjasorkes teacher is reluctant to convey the material in line with the Competence Standard and Based Competence. Related to the process health education it self, there so many teachers which use speech method, in fact this method shoul be matched with the students characteristics and school condition. Moreover, most of the learning Media and handbook that are used in school is still Students Work sheet (LKS). Keywords : Penjasorkes, health education, the process of the providing health education.